Elements of Oil and Gas Well Tubular Design - Pattillo, P. D. (Gulf Professional Publishing is an imprint of Elsevier, 2018)
"Elements of Oil and Gas Well Tubular Design addresses the fundamentals of tubular design and string characterization for analysis models, theory and algorithms in oil and gas wells. Filling the gap between the theory and field operation, this reference focuses on the mechanical design of tubing and casing. Packed with derivations, origins of tubular design, and detailed well design worked examples, this book provides the well designer with sound engineering principles applicable to today's oil and gas wells. Gives readers all they need to understand solid engineering mechanics for oil well casing and tubing design, with an emphasis on derivation, limitations and application of fundamental equations. Helps users grasp design construction from a single unified source with underlying concepts of stress, strain and material constitution. Presents tactics on how to meld practicality with detailed well design work examples amenable to quality check from commercial software"--